Participative rights in Welsh primary schools: Unpicking the policy rhetoric - Jane Williams (Policy Futures in Education, 2025)
This paper presents the findings from the initial stage of an Economic and Social Research Council (ESRC) funded project which examines the pedagogic practices that embed young children’s participative rights in lower primary classrooms in Wales. An evaluation of relevant legislation and policy in Wales from 2000 to 2022 was undertaken to explicate the positioning of teachers and their responsibilities regarding children’s participative rights. Data analysis detailed here sets out the legislative and statutory context within which teachers work, as well as the curricular and pedagogic framework which steers classroom activity. The Welsh Government has, for two decades, been explicitly sympathetic to embedding children’s rights in policy development, yet there is limited research evidencing the changes in educational curricula and practice. The gap between policy intention and implementation is not unique to Wales and therefore of universal interest. We report that although there is evidence of the increased inclusion of children’s participative rights in more recent legislation and policy, the move to education about, through and for human rights is only significantly pronounced in recent reforms such as the Curriculum and Assessment (Wales) Act 2021. We advocate that the commitment to human rights education made in the Curriculum for Wales is perpetuated and ongoing critical appraisal of legislation and policy is needed, alongside further research to understand how that commitment is being interpreted in Welsh education settings.